Resolution of Cyber Harassment Against Public Figures in the Perspective of Digital Law - Siagian, Ottow Wijanarto Tiop Ganda Pura (Universitas Negeri Gorontalo, 2022)
The purpose of this study is to examine the settlement mechanism of Cyber Harassment experienced by public figures considering that in this disruptive era of technology, more and more cases like this have emerged. The research approach method used is the statute approach and the case approach. The results of the study are that the settlement of cyber harassment disputes against public figures can be resolved through litigation and non-litigation mechanisms. It is possible to settle through this litigation route, even though in substance the legal regulations regarding cyber harassment have not been described concretely in positive law in Indonesia, departing from the understanding that there is an IUS principle. novit curia. The legal consequence, of course, is that judges are prohibited from objecting, let alone refusing a case submitted by the community and having the obligation to examine and try and give legal decisions on these legal issues. The next option apart from litigation is the non-litigation route. The author concludes that in resolving Cyber Harassment disputes against public figures if you choose a non-litigation route to be resolved, an alternative form of dispute resolution that can be used and is considered more suitable as a media for dispute resolution is mediation. Suggestion, To the Indonesian people in general and public figures in particular, must be brave to fight for their rights and make complaints or reports to the authorities so that losses arising from violations of their constitutional rights can be recovered and the state through its power tools can guarantee legal protection to victims at the same time providing a deterrent effect to the perpetrators to realize order and security in the life of society, nation, and state.